TUGAS GURU AGAMA KATOLIK DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Sihotang, Din Oloan (IN VERITATE LUX, 2019)
Religious education in schools is the duty of all Christians, especially teachers. The presence of Catholic religious teachers is the role of parents of students in developing children's faith. Catholic religious education is the church's effort to take part in the task of Jesus as Prophet, priest and King. Jesus' task as a Prophet was to teach, Catholic religious teachers were given the task and trust to form a complete human being, to educate students so that they were able to develop their faith and integrate it with everyday life. Catholic religious teachers should be able to shape students' personalities into children who believe and have good character in their daily lives. Teaching Catholic religion in schools is the duty of Catholic religion teachers. Teaching and educating is not only the transfer of knowledge of faith, but the starting point is that it can help students to know God better. Carry out activities that bring students to a place where they can know, love God and fellow humans too. Research in finding various sources of data by carrying out a quantitative approach in Catholic schools, using observation, interview and documentation techniques. The findings in this research are that the implementation of the duties of Catholic religious teachers is sufficient to form students in character values, character values ​​in relation to God, character values ​​with oneself, character values ​​with oneself and character values ​​with others. Students will better understand how to instill life values ​​in everyday life through the duties of Catholic religious teachers in Catholic elementary schools